Pediatric COVID-19 Pneumonia - Kilani, Muna; Mryyian, Amel; Dawoud, Rand (Jordan Medical Journal, 2023)
SARS-CoV-2 virus caused a pandemic that started in 2020 and infections with the virus continue to the date of this review. Children have been infected by this virus, although with less severe clinical manifestations compared to adults. Children with underlying diseases, and obesity were more susceptible to severe disease. Pediatric infection with the virus resulted systemic manifestations in addition to pneumonia. In this article we review the mechanism of lung infections, clinical manifestations, ventilation abnormalities, diagnosis, and the role of imaging and the treatment options for COVID 19 pneumonia in children